Non-agricultural activities in the economic development of the Romanian rural area - Elena Sima (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The Romanian rural economy is mainly an agricultural economy, as the share of agricultural economy is 60% compared to 14% in European Union. Most farmers practise part-time agriculture, insufficiently spending the working time on agricultural activities. In total Romanian rural area, the non-agricultural economy (SMEs in industry, services, rural tourism) has a low share, while the rural tourism, except for certain mountain zones and the Danube Delta is poorly developed. In such conditions, the paper contains an inventory of the most important methods for increasing the available time used in non-agricultural activities, as alternatives for part-time agriculture, which may become an important income source for family farms. The work relies on data processed according to the European Commission Statistics (Eurostat) and the national statistics, in order to reveal the labour force employment in agriculture. The investments in the non-agricultural and food economy, while contributing to gross value added increase through the processing of agricultural and non-agricultural raw materials from local resources, has another great advantage, by creating new jobs and by using and maintaining the local (rural) labour, revitalization of rural localities, mainly those in the less-favoured and remote rural areas.
Keywords: 330; sustainable rural development; non-agricultural activities; investments